Dampak Globalisasi terhadap Perubahan Keyakinan dan Praktik Keagamaan dalam Konteks Pluralisme Agama dan Sekularisme - Sumarta Sumarta; Zamzami Zamzami; Tenda Budiyanto; Burhanudin Burhanudin; Romlah Romlah (LPPM STAIS Dharma Indramayu, 2019)
Abstract In an increasingly interconnected era of globalization, the impact of globalization on changes in beliefs and religious practices in the context of religious pluralism and secularism has become a profound concern. This article explores the impact of globalization on the dynamics of religion and society within the framework of diverse beliefs and the separation of religion and state. We discuss how globalization has brought individuals from various religious backgrounds together in an increasingly heterogeneous society, sparking the exchange of ideas, deeper understanding of other religions, and positive interfaith dialogue efforts. On the other hand, we also highlight emerging challenges, such as the spread of extremist views and interreligious tensions. In this context, we evaluate the crucial roles of religious pluralism and secularism in managing the impact of globalization and promoting tolerance, interfaith harmony, and a better understanding of religious differences. This article provides an in-depth understanding of the complexity of interactions among globalization, religious pluralism, and secularism in shaping the framework of changes in beliefs and religious practices. Keywords: Globalization, Belief Changes, Religious Practices, Religious Pluralism, Secularism.